Budget Implementation Strategy Performance Based At The Ministry Of Religion Office Muara Enim District - Emma Yuni Zuarmi; Lin Yan Syah; Nisma Aprini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
In the implementation of performance-based budgeting, an implementation strategy is needed so that it can achieve optimal results. The purpose of this research is to find out and analyze the process of implementing performance-based budgeting, to find out and analyze what factors influence the preparation of the 2022 budget by the Office of the Ministry of Religion of Muara Enim Regency in implementing the Performance-Based Budgeting system and to find out and analyze strategies in implementing performance-based budgeting at the Office of the Ministry of Religion of Muara Enim Regency. The research uses a qualitative descriptive approach by collecting data through observation, interviews, and documentation as well as data analysis. The results of the study show that 1) Implementation of performance-based budgeting at the Office of the Ministry of Religion of Muara Enim Regency has not achieved optimal results 2) Factors that influence the implementation of performance-based budgeting at the Office of the Ministry of Religion of Muara Enim Regency include: Communication, Resources People, Attitudes and Bureaucratic Structure and 3) Strategy in implementing performance-based budgeting for the Office of the Ministry of Religion of Muara Enim Regency using the Strengths – Opportunities strategy approach. Improving Human Resources (HR), especially in the Planning section, having regular internal meetings, and in preparing the budget should be guided by the Standard Operating Procedures that have been established so that the implementation of performance-based budgeting can run optimally.